Effect of Short-Term Weight Vest Training on Muscle Strength During Soccer-Specific Drills in Amateur Player - Elsyam, Muhammad Faisal Baihaqi; Orhan, Bekir Erhan; Nirwansyah, Waristra Tyo; Prianto, David Agus (JSES : Journal of Sport and Exercise Science, 2025)
ABSTRACTS Purpose: This study aimed to examine the effect of weight vest training on lower-limb, core, and upper-body muscle strength in amateur soccer players. Materials and Methods: This quasi-experimental study employed a three-group pre-test–posttest design involving 31 male amateur soccer players randomly assigned to control (no weight vest, Group A, n = 10), 8.03 ± 0.79% weight vest (Group B, n = 10), and 11.45 ± 1.15% weight vest (Group C, n = 11) groups using stratified randomization based on baseline muscle strength. The participants had a mean height of 166.3 ± 5.7 cm, a mean body weight of 63.06 ± 6.49 kg, and a mean body mass index (BMI) of 21.42 ± 2.33 kg/m², with playing positions including defenders, midfielders, and forwards. Participants completed a five-week training program, and muscle strength was assessed using Leg Press, Sit-Up, and Push-Up tests. Participants took part in a five-week research program consisting of one week for pre-test assessments, three weeks of training intervention, and one week for posttest evaluations. Muscle strength was measured using the Leg Press, Sit-Up, and Push-Up tests. Data were analyzed using ANOVA for normally distributed variables and the Kruskal-Wallis test for non-normally distributed variables, with post hoc comparisons (p < 0.05). Effect sizes were reported using 95% confidence intervals and Cohen’s d. Result: All participants showed improved muscle strength after the intervention. Leg Press increased in all groups, with Group C (11.45 ± 1.15% weight vest) significantly higher than the control (p = 0.0322). Sit-Up performance was also highest in Group C (p ≤ 0.0071), while Push-Up showed no significant differences (p = 0.8047). Conclusion: Weight vest training during soccer-specific strength exercises effectively enhances lower-limb and core strength in amateur soccer players, especially at higher loads, but does not significantly affect upper-body strength.